PENGABDIAN SEBAGAI PANELIS SUSTAINABLE INNOVATION & ENGINEERING TECHNOLOGY EXHIBITION (SINERGIE 5.0) POLITEKNIK TUN SYED NASIR SYED ISMAIL - Jeallyza Muthia Azra (LPPM Universitas Bina Bangsa, 2023)
The Sustainable Innovation and Engineering Technology Exhibition (SINERGIE) 5.0 is a final project for students to produce creative and innovative products that can be commercialized. SINERGIE 5.0 will be held in June 2022 with the target of students in the 4th semester of the Diploma in Food Technology Polytechnic Tun Syed Nasir Syed Ismail (PTSN) Malaysia. A total of six panelists from three Malaysian industry practitioners and three Indonesian academic institutions also contributed to the assessment. Assessment is carried out on posters, videos, and question-and-answer sessions. Food innovation products developed by SINERGIE 5.0 participants already have novelty and are in accordance with the program theme, namely sustainable innovation. The improvements needed to make innovation better are related to designing formulas, presenting data, making nutrition facts, and calculating prices. Analysis of nutritional content and physical characteristics in the future needs to be done so that the data becomes more comprehensive